2019
DOI: 10.1101/2019.12.27.889402
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neuropeptide VF neurons promote sleep via the serotonergic raphe

Abstract: 15Although several sleep-regulating neurons have been identified, little is known about how they 16 interact with each other for sleep/wake control. We previously identified neuropeptide VF (NPVF) 17 and the hypothalamic neurons that produce it as a sleep-promoting system (Lee et al., 2017). 18Here we use zebrafish to describe a neural circuit in which neuropeptide VF (npvf)-expressing 19 neurons control sleep via the serotonergic raphe nuclei (RN), a hindbrain structure that promotes 20 sleep in both diurn… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Observational studies have shown that lifestyle-related risk factors, like alcohol consumption, smoking, diabetes, hypertension, cerebrovascular disease, stress, anxiety, depression, and sleep-wake dysfunction are statistical contributors to the emergence and severity of AD-type dementia. 168,169,177,178 NSS integrity is tightly linked to many of these risk factors, including sleep-wake dysfunction, [179][180][181][182] stress, [183][184][185] depression, 186,187 drug abuse, 188,189 eating disorder, 190 and diabetes. 191,192 Therefore, it is reasonable to expect that positive lifestyle changes may galvanize NSS resilience to AD.…”
Section: Non-pharmacological Interventionsmentioning
confidence: 99%
“…Observational studies have shown that lifestyle-related risk factors, like alcohol consumption, smoking, diabetes, hypertension, cerebrovascular disease, stress, anxiety, depression, and sleep-wake dysfunction are statistical contributors to the emergence and severity of AD-type dementia. 168,169,177,178 NSS integrity is tightly linked to many of these risk factors, including sleep-wake dysfunction, [179][180][181][182] stress, [183][184][185] depression, 186,187 drug abuse, 188,189 eating disorder, 190 and diabetes. 191,192 Therefore, it is reasonable to expect that positive lifestyle changes may galvanize NSS resilience to AD.…”
Section: Non-pharmacological Interventionsmentioning
confidence: 99%